KECERNAAN KULIT DAGING BUAH KOPI DENGAN FERMENTASI MOL (MIKROORGANISME LOKAL) DALAM RANSUM PELET PAKAN KELINCI PERANAKAN REX - FATHI NASUTION (Universitas Sumatera Utara, 2015)
ABSTRACT This research was conducted at the Laboratory of Biologi Ternak, University of Sumatra Utara on June 2014 until August 2014. This study aims to determine the effect of utilization fermented coffee pulp to dry matter and organic matter. This study used 20 male rex rabbits with average weight 913.05 g ± 60.49 g. The design used a completely randomized design (CRD) with 4 treatments and 5 replications. The treatments were diet containing fermented : non-fermented coffee pulp with ratio on treatment P0 (0%: 30%); P1 (10%: 20%); P2 (20%: 10%); and P3 (30%: 0%). The variable were observed that Dry Matter Digestibility (DMD) and Organic Matter Digestibility (OMD). The results showed that the average dry matter digestibility (%) on treatment P0, P1, P2, and P3 were 59.70; 59.75; 59.74; and 59.89, repectively, while the average organic matter digestibility (%) 61.28; 61.40; 61.31; and 61.50, respectively. The result statistical analysis indicated that treatment were not significant affect (P>0.05) on Dry Matter Digestibility (DMD) and Organic Matter Digestibility (OMD). The conclusion of this study is fermented LMO (local micro organisme) has not significant effect on digestibility on rex rabbit. Keywords : Digestibility, Coffee Pulp, Fermentation with LMO, Rex Rabbit.